Exploiting the damaging effects of ROS for therapeutic use by deactivating cell-free chromatin: the alchemy of resveratrol and copper - Mittra, Indraneel (Frontiers in Pharmacology, 2024)
Cell-free chromatin particles (cfChPs) that circulate in blood, or those that are released locally from dying cells, have myriad pathological effects. They can horizontally transfer themselves into healthy cells to induce DNA damage and activate inflammatory and apoptotic pathways. It has been proposed that repeated and lifelong assault on healthy cells by cfChPs may be the underlying cause of ageing and multiple age related disorders including cancer. The damaging effects of cfChPs can be minimized by deactivating them via the medium of ROS generated by admixing the nutraceuticals resveratrol (R) and copper (Cu). The antioxidant R acts as a pro-oxidant in the presence of Cu by its ability to catalyse the reduction of Cu(II) to Cu(I) with the generation of ROS via a Fenton-like reaction which can deactivate extra-cellular cfChPs. This perspective article explores the possibility of using the damaging potential of ROS for therapeutic purposes. It discusses the ability of ROS generating nutraceuticals R-Cu to deactivate the extracellular cfChPs without damaging effects on the genomic DNA. As cfChPs play a key role in activation of various disease associated pathways, R-Cu mediated deactivation of these pathways may open up multiple novel avenues for therapy. These findings have considerable translational implications which deserve further investigation by the way of well-designed randomised clinical trials.